Challenging the Practice of Administrative Detention for Stateless Persons in South Africa - Khan, Fatima (African Human Mobility Review, 2023)
In South Africa section 41 of the Immigration Act requires any person approached on reasonable grounds by a police or immigration officer to identify themselves either as a citizen or as a person lawfully present in the Republic. Anyone unable to identify themselves as persons lawfully in South Africa will be deemed to be illegally present and hence subject to an arrest, detention, and possible deportation. This detention can go on for an initial period of 120 days. This “unlawful” status automatically entitles immigration officials to arrest and detain such persons, but with the caveat that if such persons express an intention to apply for refugee status their asylum application must be permitted and facilitated. Stateless persons are, by definition, unable to demonstrate their legal presence or provide a valid identity document. They would therefore be deemed to be unlawfully present and therefore detained. This section of the Immigration Act is especially prejudicial to stateless persons since South Africa has no status determination procedure for stateless persons. This paper intends to demonstrate the unlawfulness of the laws regarding the immigration detention of stateless persons and whether there is an alternative approach or a remedy that could be implemented for stateless persons arrested without the means to identify themselves in South Africa.